Prospects for decent work in services - Sameer Khatiwada; John Paul Flaminiano (Asian Development Bank Institute (ADBI), 2019)
This paper examines how the services sector could provide decent and gainful employment in developing Asia. Using living wages as a reference point, this paper reports that a significant portion of the workforce in developing Asian economies, the majority of which are employed in the agricultural sector, are not living wage earners. On the other hand, manufacturing, and to a larger extent, services, are able to provide their workforce with good jobs. Economies that are more successful at moving workers from low- to high-productivity sectors have done better on job creation accompanied with improved productivity, higher wages, and large reductions in poverty. Recent developments of information and communication technology industries, as in the case of India and the Philippines, is a striking example of how developing economies can open up business opportunities through global outsourcing of tradable labor. This paper highlights the importance of improving human capital through education and upskilling, as well as physical and digital infrastructure, to address the large supply of low-productivity and informal sector workers in developing Asia, and to provide new and gainful employment opportunities.
Keywords: L80; J30; O14; O40; O47; O53; 330; decent jobs; modern services; living wages; technology; tradability